Analisis Metode CAPM (Capital Asset Pricing Model) Dalam Menentukan Investasi Saham (Pada Perusahaan Sub Sektor Asuransi Umum Di Bursa Efek Indonesia) - Muhammad Shaflly (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the performance of insurance sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 using the Capital Asset Pricing Model (CAPM). The model is employed to calculate the expected return based on systematic risk, measured by the beta (β) parameter. In this study, stocks are categorized as efficient if their individual return is higher than the expected return calculated using CAPM. Conversely, stocks with lower returns than expected are considered inefficient. The findings reveal significant variations in the stock returns of insurance companies listed on the IDX. Some stocks were found to be efficient as they provided higher returns than expected, while others were inefficient, such as Asuransi Tugu Pratama Indonesia Tbk. (TUGU), which provided lower returns than expected. This study also identifies that stocks with higher betas are riskier but potentially provide higher returns, while stocks with lower betas tend to be more stable with smaller returns. The findings offer guidance for investors in selecting efficient stocks, considering both key factors: risk and expected return. Therefore, the use of the CAPM method is expected to provide a stronger basis for more rational and informed investment decision-making for investors in the Indonesian capital market, particularly in the insurance sector.